Parasite species co-occurrence patterns on North American red squirrels (Tamiasciurus hudsonicus) - Jasmine S. M. Veitch; Jeff Bowman; J. Dawson Ketchen; Albrecht I. Schulte-Hostedde (Parasitology)
Parasite species interactions, host biology traits, and external environmental factors can drive co-occurrence patterns between parasite species. We investigated co-occurrence patterns between three ectoparasite species (mite (Neotrombicula harperi), and fleas (Orchopeas caedens and Ceratophyllus vison)) of North American red squirrels (Tamiasciurus hudsonicus). We evaluated (1) whether ectoparasites of red squirrels exhibit non-random co-occurrence patterns, and (2) the contribution of host and external environmental factors to parasite co-occurrence. Bayesian ordination and regression analysis (boral) revealed random associations between parasite species pairs when accounting for host and external environmental factors. However, the mite N. harperi exhibited a negative association with the flea O. caedens and positive association with the flea C. vison linked to temporal patterns of occurrence. Our data suggests that parasites of the investigated population of red squirrels tend to form associations based on temporal trends in infestation rather than species interactions. Further experimentation should investigate the role of additional factors on parasite co-occurrence patterns, such as temperature, precipitation, and humidity.